PENGARUH PEMBERIAN TERAPI KOMPLEMENTER AIR HANGAT PADA REMAJA YANG MENGALAMI DISMENOREA DI DESA MALEI, KABUPATEN POSO - Rasiman, Noviany Banne; Nuraliyah; Chely Veronica Mauruh (Pustaka Katulistiwa : Karya Tulis Ilmiah Keperawatan, 2024)
Adolescence is the early period of sexual maturity, in this period a child experiences physical, hormonal, and sexual changes that can carry out the reproductive process. Based on interviews conducted on 3 teenagers in Malei Village, two of them said that when they menstruated they felt moderate menstrual pain, other teenager said that when they menstruated they felt heavy menstrual pain, and it interfered with their activities. The purpose of this study was to determine the effect of warm water compress complementary therapy on dysmenorrhea in teenagers at Malei Village, Poso Regency. The research design using quantitative with a pre-test-post-test group only design. The data using primary data and secondary data. Data analysis using univariate and bivariate. The population in this study were adolescents aged 12-17 years in Malei Village totaling 46 people. The sample was 32 respondents. The sampling technique used purposive sampling. The results of the study showed that the average pain of respondents before being given warm compresses was 56.3% on a moderate scale, the average pain of respondents after being given warm compresses was 90.6% on a mild scale. There is a difference, before and after warm compresses with P = 0.000 (p <0.05). The conclusion, there is an effect of complementary therapy of warm water compresses on dysmenorrhea pain in adolescents. The suggestions, the researcher hope that the result of this studycan be use as a reference material to be using as one part of the intervention to reduce pain in adolescents who experience dysmenorrhea.